Thermodynamic analysis of the thermal-technological complex of sugar production: criteria for energy efficiency of an enterprise - Samiilenko, Sergii; Bondar Vоlоdymyr; Piddubnyi, Volodymyr; Bilyk, Olena; Shutyuk, Vitaliy; Fedoriv, Viktor (Eastern-European Journal of Enterprise Technologies, 2021)
A procedure for analyzing the effectiveness of using fuel and energy resources (FER) in sugar production, based on the developed idealized circuit of the thermal-technological complex (TTC) as the base for comparison was presented. This procedure makes it possible to quantify the level of perfection of existing and proposed thermal circuits, as well as the impact of measures for enhancing energy efficiency on their perfection. By idealizing technological and energy processes, a hypothetical TTC was synthesized, for which the minimum possible energy and entropy characteristics are determined. Under these conditions, the minimum possible heat consumption for the implementation of technological processes according to the classical heat technology circuit was calculated – 118.40 MJ/t; a "minimum" total increase in entropy from irreversible processes of the HTC – 314.68 kJ/(t·K); a minimum complex magnitude of specific consumption of conventional fuel – 0.8 % to m. b. The determined characteristics are absolute criteria for the efficiency of sugar production systems, since it is impossible to reach lower values under existing technology, quality of raw materials and other conditions. The content of the criteria of energy efficiency of TTC was stated and the system of coefficients was proposed: coefficient of total energy efficiency of the TTC, coefficient of energy efficiency of the system of heat supply of the technological processes and coefficients of energy efficiency of internal and external structures of the TTC. The proposed criteria provide an objective and thermodynamically correct characteristic of the TTC of different structures. The presented results of analysis of various measures for increasing the energy efficiency of sugar production show that only a gradual comprehensive reconstruction of an enterprise makes it possible to consistently reduce the FER consumption for technological needs, approaching the boundary values.